Mengembangkan media kolase berbasis lingkungan untuk meningkatkan kemampuan kognitif anak usia dini - Jimmi Morgan Sihombing; Aman Simaremare; Winara Winara (Universitas Pendidikan Indonesia, 2026)
The underdevelopment of cognitive abilities in early childhood is caused by the use of less engaging learning media. Appropriate efforts and strategies are needed to address problems arising from innovation in teaching and learning activities. This study aims to produce environmentally based collage media to improve the cognitive abilities of children aged 5-6 years at Pembina Siborongborong Kindergarten. The research type used is Research and Development (RnD) with a 4D model. The research subjects included three validators, 30 children, and the class teacher at Pembina Siborongborong Kindergarten. The results of the study indicate that the environmentally based collage media is very good and feasible to use. In addition, this media is proven effective because it shows an increase in average pretest and posttest scores, which are in the high category. The practicality of the media is also classified as very good based on teacher and student responses. The use of environmentally based collage media has been shown to help teachers improve children's cognitive abilities and make it easier for them to understand material on fruit names, characteristics, and size comparisons.